2010
DOI: 10.1007/s12094-010-0527-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy of lymphoma using histone deacetylase inhibitors

Abstract: In this study, we reviewed epigenetic therapy of lymphomas using histone deacetylase inhibitors (HDACi), a promising new class of antineoplastic agents. Epigenetic therapy, a new therapeutic concept, consists of the use of HDACi and or DNA methyltransferase inhibitors (DNMTi). We conducted a comprehensive review of the literature for antitumour activity of HDACi and its mechanism of action. HDACi modify the expression of several genes related to cancer development, which can result in antineoplastic activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…3C). Consistent with earlier reports of other HDAC inhibitors (15,(19)(20)(21), we observed that CUDC-907 and panobinostat induced cell-cycle arrest at G 2 -M phase. In contrast, the PI3K inhibitors GDC-0941 and BEZ-235 predominantly induced G 0 /G 1 cell-cycle arrest ( Fig.…”
Section: Cudc-907 Induces Apoptosis and G 2 -M Cell-cycle Arrest In Csupporting
confidence: 93%
“…3C). Consistent with earlier reports of other HDAC inhibitors (15,(19)(20)(21), we observed that CUDC-907 and panobinostat induced cell-cycle arrest at G 2 -M phase. In contrast, the PI3K inhibitors GDC-0941 and BEZ-235 predominantly induced G 0 /G 1 cell-cycle arrest ( Fig.…”
Section: Cudc-907 Induces Apoptosis and G 2 -M Cell-cycle Arrest In Csupporting
confidence: 93%
“…For instance, HDACi and DNMT inhibitors have been tested for the treatment of aggressive non-Hodgkin's Lymphomas (NHLs) [136][137][138][139][140][141][142][143][144][145].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…This data provided the structural basis for the catalytic mechanism and the inhibition of this family of enzymes, paving the way for the design of new bioactive molecules able to interfere with the deacetylation reaction. Several compounds targeting HDACs entered clinical trials in the last year and have been reviewed elsewhere [98,105,139,141,234,237,[240][241][242][243]. These proteins belong to the open / folding class, with an eight-stranded parallel -sheet sandwiched between -helices.…”
Section: Class I Ii and Iv Deacetylasesmentioning
confidence: 99%
“…Class I, II, and IV HDACs require zinc for their enzymatic activity, whereas class III HDACs, also known as silent informant regulator proteins (sirtuins), require nicotinamide adenine dinucleotide (NAD + ) as a coenzyme for their activity. [8][9][10] HDAC inhibitors are a chemically broad group of molecules found to inhibit the activity of HDACs at a wide range of concentrations, from low nanomolar to high millimolar levels. To date, there are several HDAC inhibitors in development, with the focus on greater potency and improved tolerability.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%